STRATEGI DINAS PARIWISATA DAN KEBUDAYAAN DALAM MENGEMBANGKAN PARIWISATA DI KABUPATEN SINJAI - Haerunnisa, Andi; Madani, Muhlis; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2024)
The purpose of this research is to find out some of the strategies of the tourism and culture department in developing tourism in Sinjai district. This study uses a qualitative descriptive qualitative method. Data collection techniques include observation (observation), interviews (interviews) and documentation. The results of the research are that tourism development strategies in Sinjai district implemented by the government really need the full support and participation of the existing community in the end it is hoped that a conducive tourism climate can be realized for the growth and development of competitive Indonesian tourism. Empowerment of the Sinjai district tourism office towards resources includes two parts, namely empowerment of human resources and natural resources.